Analysis of the Relationship between Sleep Environment and Sleep Quality in Children with Cancer in the Chemotherapy Phase - Nita Priyanti; Retno Palupi Sedyowati (Global Writing Academica Researching & Publishing, 2023)
The study was conducted to analyze the relationship to find out whether there is a correlation between the sleep environment and sleep quality of children with cancer in the chemotherapy phase. The results of this study will help determine the steps to be taken to improve the bed environment and improve the quality of sleep of children with cancer in the chemotherapy phase. In this study, the method that will be used to conduct research is quantitative research, because it tests hypotheses using certain statistical analysis tools. Quantitative data is statistical data in the form of numbers, both directly extracted from research results and the results of processing qualitative data into quantitative data. This study found that sleep environment and children's sleep quality have a significant relationship. The results show that a good sleep environment, including a comfortable temperature, low noise, and dim lighting, contributes to better sleep quality in children. In addition, other factors such as the comfort of the bed and a regular sleep schedule also affect the quality of a child's sleep.